Synthesis and Characterization of Silver Nano Particles from Aqueous Leaf Extract of Diospyrosebenum (J.Koeniig) along with the evaluation of its Biopotency (International Journal of Food and Nutritional Sciences, 2022)
In the present study, the silver nanoparticles (AgNPs) were synthesized from aqueous leaf extract of Diospyrosebenum and characterized by UV–visible spectroscopy, FT-IR, SEM, TEM, EDX analysis. The results proved that the biosynthesized nanoparticles were uniformly dispersed, spherical shaped with an average particle size of 34 nm and with an atomic silver percentage of 79.13. In three planes, XRD was calculated to investigate the crystallinity and consistent spherical size (peaks at 2θ values of at 39.30, 44.50, 63.70 and 77.90) of the particles.The phytochemical and FT-IR analysis showed the presence of phenols, terpenoids and alkaloids in the synthesized AgNPs. The synthesized AgNPs exhibited significant free radical scavenging activity.Antibacterial properties of AgNPs were evaluated against clinically significant multidrug-resistant strains of two gram positive bacteria (Bacillus subtilis, Bacillus cereus), two-gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa). AgNPs indicated significant antibacterial activity against pathogens tested.Significant antioxidant activity with an IC50 value of 72.66 μg/mL which was very close to standard (IC50 is 62.49 μg/mL). The synthesised AgNPs show remarkable anti-inflammatory and anti-diabetic activity. As a consequence, biosynthesized Diospyrosebenumextract mediated AgNPs shown outstanding effects and have the potential to be used as antibacterial, antioxidant, anti-inflammatory and anti-bacterial agents.